2020
DOI: 10.1021/acs.orglett.0c03038
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Radical Addition/Annulation to Construct Phenylsulfonyl-Functionalized Dihydrobenzofurans Involving an Intramolecular 1,5-Hydrogen Atom Transfer Process

Abstract: A visible light-induced radical cascade reaction of 2-alkynylarylethers with sodium sulfinates was established for the synthesis of sulfonyl-functionalized dihydrobenzofurans, and an intramolecular 1,5-hydrogen atom transfer was involved in this transformation. This process provided an efficient and convenient C–C formation protocol for the construction of a dihydrobenzofuran ring. Various substituents on 2-alkynylarylethers and sodium sulfinates were tolerated in the reaction, and the corresponding products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…To establish approaches to synthesizing 2,3-multisubstituted analogies with tetrasubstituted carbons, synthetic communities have developed numerous efficient methods …”
Section: Introductionmentioning
confidence: 99%
“…To establish approaches to synthesizing 2,3-multisubstituted analogies with tetrasubstituted carbons, synthetic communities have developed numerous efficient methods …”
Section: Introductionmentioning
confidence: 99%
“…1-(Benzyloxy)-2-ethynylbenzene ( 18b ) 103 : Synthesised from 1-(benzyloxy)-2-iodobenzene (620 mg, 2 mmol) according to the general procedure ( I ) to afford the title compound as an oil (291 mg) in 70% yield. 1 H NMR (400 MHz, CDCl 3 ) δ 7.59 7.47 (m, 3H), 7.41 − 7.15 (m, 5H), 6.99 − 6.86 (m, 1H), 5.23 (s, 2H).…”
Section: Methodsmentioning
confidence: 99%
“…Considering that a Csp 3 –Br bond is much weaker than a Csp 3 –F bond (BDE = 250 ± 50 kJ mol –1 for Csp 3 –Br), we envisioned that the radical β-bromo fragmentation of β-bromo fluoroalkyl radicals could proceed under mild conditions and provide valuable fluoroalkenes. Recent works have demonstrated that the radical addition–translocation–cyclization (RATC) of easily accessible alkynes represents an appealing strategy for the preparation of highly substituted cyclic scaffolds. More importantly, the RATC process results in a C-radical at the carbon atom where initial radical addition occurs, which we believe can serve as an efficient pathway to the above-mentioned β-bromo fluoroalkyl radical intermediates. In our reaction design depicted in Figure c, the single-electron reduction of a dibromofluoroalkane of type 2 , many of which are commercially available, by a photocatalyst generates the corresponding monobromofluoroalkyl radical, which then engages in a radical addition–translocation–cyclization cascade with alkyne 1 to generate the key fluoroalkyl radical intermediate II .…”
mentioning
confidence: 97%